2020
DOI: 10.1111/ncn3.12415
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease therapy with Istradefylline and blood biomarkers of epigenetics

Abstract: Background Istradefylline (IST), an adenosine A2A receptor antagonist, has been used since 2013 in Japan as an adjunctive therapy to levodopa (L‐DOPA) for patients with Parkinson's disease (PD). The long‐term use of IST as an adjunct to L‐DOPA (IST‐LD) was herein investigated to clarify the cooperative potential to keep motor functions, and an epigenetic modification for disease‐specific up‐regulated A2AR signals. Methods The cohort comprising 62 PD patients with diurnal variations in motor function were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…On this basis, the istradefylline-induced epigenetic suppression of A 2A receptor upregulation may have interesting implications for the fundamental goals of LD therapy, although many areas remain to be investigated, including PET imaging of dopamine transporters and A 2A receptors in patients with PD receiving long-term istradefylline treatment [24][25][26][27][28][29][30]. If increased A 2A receptor expression in the indirect pathway contributes to the need for progressive increases in LDD, A 2A receptor epigenesis [21] data and the present real-world evidence (RWE) findings may explain the mechanism underpinning this correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, the istradefylline-induced epigenetic suppression of A 2A receptor upregulation may have interesting implications for the fundamental goals of LD therapy, although many areas remain to be investigated, including PET imaging of dopamine transporters and A 2A receptors in patients with PD receiving long-term istradefylline treatment [24][25][26][27][28][29][30]. If increased A 2A receptor expression in the indirect pathway contributes to the need for progressive increases in LDD, A 2A receptor epigenesis [21] data and the present real-world evidence (RWE) findings may explain the mechanism underpinning this correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ADORA2A , the A 2A receptor gene, is subject to post-transcriptional silencing in individuals without PD [22,23]. Demethylation (activation) of ADORA2A , which has been observed in PD and may contribute to the observed increase in A 2A density, was reversed after 12 months of istradefylline treatment [21]. Although how or whether A 2A receptor dynamics in peripheral lymphocytes can be correlated with brain A 2A receptors remains to be investigated, based on these findings, it could be hypothesized that 1) over time, upregulation of A 2A receptor expression may contribute to symptomatic progression of PD, resulting from promoting imbalance of basal ganglia, and 2) the need to maintain a clinically effective level of dopamine stimulation by, for example, progressively increasing LDD, could be relieved by addition of istradefylline to selectively inhibit A 2A receptor function, thereby relieving motor dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This pathophysiological change may contribute to the need for increases in dopaminergic treatments such as LD over the course of disease progression of PD. Although there is no study to date addressing whether A 2A receptor antagonists can induce a change in A 2A receptor expression patterns in the brain, it has been reported that expression of A 2A receptors in peripheral blood lymphocytes, which is increased in patients with PD (naïve to istradefylline treatment) [20], can be restored to levels comparable to those in healthy controls after 12 months of istradefylline treatment [21]. Furthermore, ADORA2A, the A 2A receptor gene, is subject to post-transcriptional silencing in individuals without PD [22,23].…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, ADORA2A, the A 2A receptor gene, is subject to post-transcriptional silencing in individuals without PD [22,23]. Demethylation (activation) of ADORA2A, which has been observed in PD and may contribute to the observed increase in A 2A density, was reversed after 12 months of istradefylline treatment [21]. How or whether A 2A receptor dynamics in peripheral lymphocytes can be correlated with brain A 2A receptors remains to be investigated.…”
Section: Plos Onementioning
confidence: 99%
“…Because higher expression levels of A2A receptor are present in PD patients, (Varani et al, 2010) SAM therapy can be tried as a vital therapeutic tool in these patients to decrease the expression of A2A receptors by increasing the methylation of the ADORA2A gene (Buira et al, 2010b). Chronic therapy with A2A receptor antagonist istradefylline as an adjunct to L-DOPA (IST-LD) for PD patients revealed to restore higher demethylation of ADOA2AR, resulting in reduced expression of A2A receptor in the striatum (Kanzato et al, 2020).…”
Section: Epigenetic Study Of Adora2a Genementioning
confidence: 99%